Estudio socio económico de pequeños productores de arroz (Oryza sativa L.), y comercialización en el mercado interno de la provincia de Los Ríos - Yépez Macías, Jean Carlos (2019)
The present work was carried out with the purpose of evaluating and determining the economy of small rice producers, a survey of small rice producers was conducted where, prior to a field analysis, we found that there are a number of shortcomings where the farmer does not count with technical training for rice production and at the same time the lack of direct marketing without intermediaries for a fair payment of their crops. We have carried out surveys of 20 small rice producers in order to know their concerns with respect and based on their responses we have prepared the analysis in tabulated form where we draw our conclusions about it. The analysis of this project aims to ensure that small rice producers join together to obtain benefits such as continuous training and the direct sale of their crops without intermediaries since together they would fulfill the quota allocated by the warehouse and through this union they would achieve the expected gains and improving your lifestyle